Synthesis, structural characterization, and thermal properties of Ca‐ and La‐doped soda‐lime glasses by laser melting. (20th April 2020) - Ali, Sharafat; Wójcik, Natalia A.; Jonson, Bo; Kamitsos, E.I.; Li, Xinghua; Luo, Jian; Möncke, Doris
ABSTRACT: Laser melting techniques have been used in the preparation of unconventional glass compositions with high melting temperatures. Thus, we wanted to test the feasibility of using a CO2 laser in the preparation of nitrogen‐rich oxynitride glasses and nitride silicate glasses. Melting from oxides and metallic raw materials, we wanted to study first glass formation and possible evaporation losses of the glass components. Two glass series were prepared and studied for their structure and thermal properties, one with Ca 2+ ‐ and a higher melting La 3+ ‐doped soda‐lime‐silicate (SLS) series. In less than 3 minutes of laser melting, spheres of up to 6 mm diameter were successfully fabricated. The obtained glass samples were homogeneous and transparent in the visible region. X‐ray diffraction and Raman spectroscopic analysis confirmed the amorphous nature of the synthesized samples. Sodium losses increase as calcium is added to the soda‐lime‐silicate glass. As expected, increasing Ca 2+ or La 3+ addition lead to increased depolymerization of the silicate network. Moreover, the increases in T g with the addition of Ca 2+ or La 3+ ions indicating strengthening of the soda‐lime‐silicate glass by increasing strength of the M‐O bonds of divalent and trivalent ions over monovalent sodium ions, weak Na‐O bonds also resulting in significant evaporation loss during the short laser melting times. The thermal stability decreases upon addition of Ca 2+ or La 3+ ions to the soda‐lime‐silicate glasses.